The Development of Snack Bars from Salak Seed Flour and Red Beans as Potential Supplementary Food for Anemic Adolescent Girls - Liana, Gladya Lady; Indarto, Dono; Suselo, Yuliana Heri (Media Publikasi Cendekia Indonesia, 2025)
Anemia is a condition in which the body experiences a lack of Hb in the blood. One of the causes of anemia is the need for iron and protein that is not fulfilled by the daily intake. Snake fruit seed flour and red beans have high potential to be developed into health-beneficial products such as snacks. The purpose of this study was to develop snack bars as a treatment for anemia in adolescent girls and to analyze hedonic tests, microbiological contamination, and nutritional content. The data analysis used was the Kruskal-Wallis test with Dunn's Post-Hoc test. This study shows that the snack bar formulation of snake fruit seed flour and red bean has a statistically significant effect with a p-value <0.05. Based on the level of liking of high school adolescent girls, the most preferred formulations are formulations P0 and P3. The P0 treatment has nutritional content (carbohydrate 43.33%, protein 14.30%, fat 19.70%, total calories 400 Kcal, iron 3.6 mg, vitamin C 24.5 mg, and zinc 4.8 mg) and the P3 formulation has nutritional content (carbohydrate 49.49%, protein 10.71%, fat 13.53%, total calories 360 Kcal, iron 11.4 mg, vitamin C 28.0 mg, and zinc 5.2 mg), so it has the potential to innovate supplementary feeding for anemic adolescent girls.